2010
DOI: 10.2196/jmir.1550
|View full text |Cite|
|
Sign up to set email alerts
|

How Patients With Schizophrenia Use the Internet: Qualitative Study

Abstract: Background The Internet is an important source of health information for people with psychiatric conditions. Little is known about the way patients with schizophrenia use the Internet when it comes to issues related to their illness. Data on their specific needs, difficulties, and the consequences related to Internet use are lacking.Objective Our objective was to investigate the nature and subjective consequences of health-related Internet use among patients with schizophrenia.Methods In all, 26 individual sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
142
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 31 publications
11
142
3
Order By: Relevance
“…In accordance with previous studies [4,11,22] and with our third hypothesis, the majority of patients reported positive experiences related to internet usage. However, 22.7% (22/97) of the patients felt frustrated or anxious in relation to the internet, and…”
Section: Experiences and Opinions About The Internetsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous studies [4,11,22] and with our third hypothesis, the majority of patients reported positive experiences related to internet usage. However, 22.7% (22/97) of the patients felt frustrated or anxious in relation to the internet, and…”
Section: Experiences and Opinions About The Internetsupporting
confidence: 93%
“…However, in accordance with our hypotheses and with previous studies [10], the FEP patients used this resource to a greater extent than the suggest that despite the fact that the internet is an accessible and fast resource to obtain information [18,22], patients still rely on clinicians as their first source of health information.…”
Section: Use Of the Internet Related To Mental Healthsupporting
confidence: 90%
See 1 more Smart Citation
“…The Internet has also become a powerful source of information and support for patients with psychosis (Haker et al, 2005), with the potential to significantly influence health related behaviors and decisions as well as the clinician-patient relationship (Schrank et al, 2010). Emerging evidence indicates that the use of the Internet by people with psychosis resembles that of individuals not affected by mental illness (Haker et al, 2005;Schrank et al, 2010). People with psychosis use the Internet effectively to create social connections enabling the development of both virtual and face-to-face relationships (Spinzy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…People with psychosis use the Internet effectively to create social connections enabling the development of both virtual and face-to-face relationships (Spinzy et al, 2012). In addition to the general advantages such as accessibility and the capacity to access a wide array of resources (Fox and Rainie, 2000), people with psychosis resort to the Internet because of the anonymity and absence of a hierarchy on the Web and its potential to assist in overcoming difficulties with social interaction (Schrank et al, 2010).…”
Section: Introductionmentioning
confidence: 99%